2015
DOI: 10.1107/s1600576714027824
|View full text |Cite
|
Sign up to set email alerts
|

Real structure of Ge4Bi2Te7: refinement on diffuse scattering data with the 3D-ΔPDF method

Abstract: Metastable Ge 4 Bi 2 Te 7 is highly disordered; the average structure corresponds to the rocksalt type. The diffraction pattern shows diffuse streaks interconnecting Bragg reflections along all cubic h111i directions. These streaks exhibit satellitelike maxima and arise from vacancy ordering in non-periodically spaced defect layers. The atom layers near these vacancy layers are displaced with respect to the average structure: they tend to form -GeTe-type double layers. The threedimensional difference pair dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(35 reference statements)
1
9
1
1
Order By: Relevance
“…Figure and Tables S5 and S6 in the Supporting Information) clearly reveal NaCl‐type average structures. As discussed earlier, such a symmetrical model is appropriate although quenching the NaCl‐type HT phase of GST materials yields samples with multiply twinned layer‐like domains, because their size is in the range of the X‐rays' length of coherence and the Te‐atom substructure retains its cubic ABC stacking sequence. No significant deviations from cubic metrics or symmetry were detected in tentative refinements using a α‐GeTe‐type structure model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure and Tables S5 and S6 in the Supporting Information) clearly reveal NaCl‐type average structures. As discussed earlier, such a symmetrical model is appropriate although quenching the NaCl‐type HT phase of GST materials yields samples with multiply twinned layer‐like domains, because their size is in the range of the X‐rays' length of coherence and the Te‐atom substructure retains its cubic ABC stacking sequence. No significant deviations from cubic metrics or symmetry were detected in tentative refinements using a α‐GeTe‐type structure model.…”
Section: Resultsmentioning
confidence: 99%
“…These defect layers apparently reduce the phononic part κ p of the thermal conductivity . The fact that the average structure of such compounds corresponds to the NaCl type implies a “cubic” ABC stacking sequence of the Te‐atom layers around the defect layers, in contrast to a “hexagonal” ABA sequence around the van der Waals gaps of stable layered trigonal phases. Compounds with n = 12 or 19 reach ZT values of up to 1.5 or 1.3 at 450 °C, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The 3D-ÁPDF thus contains information on the deviation of the local structure from the average crystal structure. The method allows for extensive, fast and fairly general modelling of diffuse scattering (Simonov, 2014;Simonov et al, 2014a,b;Urban et al, 2015). The technique depends on the measurement of a complete three-dimensional scattering data set.…”
Section: Introductionmentioning
confidence: 99%
“…In a progression to a more quantitative analysis, short-range ordering parameters were successfully refined from the 3D-ÁPDFs (Simonov et al, 2014b;Urban et al, 2015). Later studies have revealed short-range ionic correlations in the intercalation compounds 0 -Na 0.45 V 2 O 5 (Krogstad et al, 2020) and local structure effects in the thermoelectric -Cu 2Àx Se (Roth & Iversen, 2019).…”
Section: Introduction 1backgroundmentioning
confidence: 99%